DFT study of the electronic properties and gas sensing characteristics of the novel Ag2O modified BP/BSe van der Waals heterostructures - Amirali Abbasi (Scientific Reports)
Abstract In this paper, the electronic and adsorption properties of Ag2O metal oxides modified BP/BSe van der Waals heterostructures were investigated using density functional theory calculations. The adsorptions of CO, N2O, NO and NO2 gas molecules on the Ag2O modified BP/BSe heterostructures were examined to evaluate their sensing abilities. The largest binding energy (− 1.72 eV) is observed for the binding of Ag2O to the center of BSe hexagon at the hollow sites. The Ag atoms are covalently bonded to the nearest Se atoms, as confirmed by the accumulation of charge density in the CDD diagrams between the Ag and Se atoms. We found that the NO2 adsorption on the Ag2O-BP/BSe heterostructure exhibits the highest adsorption energy of − 2.64 eV, which can verify the strong chemisorption of NO2 molecule on the heterostructure system. The changes in the band structures and work functions indicate the great effects of gas adsorption on the electronic properties of studied heterostructures. The N–O distance between the N atom of NO2 molecule and the O atom of Ag2O is 1.35 Å. It can be concluded that Ag2O modification can greatly improve the adsorption capacity of BP/BSe heterostructures. Our theoretical results clearly highlight the potential application of novel Ag2O metal oxide modified BP/BSe heterostructures in sensing gas molecules.